KEWIRAUSAHAAN MANTAN TENAGA KERJA INDONESIA STUDI PERANAN HJ. SITI DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA SUGIHAN KECAMATAN SOLOKURO KABUPATEN LAMONGAN - Khusnan Khusnan (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2021)
This study aims to know how entrepreneurship efforts undertaken by former Indonesian workers in the village Sugihan. In addition the research also aims to understand the extent of the former labor done by Indonesia and its relevance to all islamic. This study use the descriptive qualitative method. Data collection techniques used in this research was observation, interviews and documentation. The research really shows that the village Sugihan subdistrict Solokuro to work as labor indonesia is economic factors lack of jobs, and cheap eward for labor in Indonesia. With successive Hj. Siti being in indonesian workers used as capital to open a business furniture. Through effort furniture, Hj. Siti an effort for community empowerment by employing the former indonesian workers who fails and the are unemployed. As for relevance to da'wah community development of islam is to create a society that is prosperous and can reach its destination of life.